Two new compounds from the marine sponge derived fungus Penicillium chrysogenum. Issue 20 (17th October 2020) - Han, Xiao; Li, Pinglin; Luo, Xiangchao; Qiao, Dan; Tang, Xuli; Li, Guoqiang
Abstract: Two new compounds (1 and 2 ) were isolated from the marine sponge derived fungus Penicillium chrysogenum by using various column chromatography techniques. Their structures were elucidated by extensive analysis of spectroscopic data and quantum chemical calculation. Compound 1 exhibited moderate activity against PTP1B with 2.95 ± 0.97% at the concentration of 30 μmol·L −1 . Abstract :